The Role Equality of Nyai in the Development of Islamic Boarding School (Pesantren) : (Case Study of Al-Huda Islamic Boarding School, Doglo, Cepogo, Boyolali Regency) - Moh. Mahbub; Kamila Adnani (BUANA GENDER : Jurnal Studi Gender dan Anak, 2022)
The hegemony of the Islamic boarding school (pesantren) has been related to the power of a Kiai. Nowadays, it has been changed by gender equality between Nyai and Kiai in Islamic boarding schools. A Kiai or Nyai can play a role inside or outside of the Islamic boarding school (pesantren). The role of the Kiai as a teacher, caretaker, and owner of the Islamic boarding school (pesantren) is quite dominant. In fact, it is found that a Nyai can also play a role in the development of education, economy, and relations in Islamic boarding schools (pesantren). This study applied a qualitative method with a phenomenological-constructionist approach. Data Collection Techniques were conducted by observation, interview, and documentation. The research results explained that the roles equality of Kiai and Nyai are obtained through a process of adaptation and the existence of space allowing the division of tasks between Kiai and Nyai as the efforts in developing Islamic boarding schools (pesantren).